La dialéctica del feminismo contemporáneo - Flores Quelopana, Gustavo (2011)
Through the analysis of what the author considers what feminist generations are, the evolution of their fundamental guidelines is explained in this article. In such way, he considers that the first feminist generation was marked by the male partiality, so the egalitarian feminism was engaged by the masculine imitation, while the second feminist generation even suggested the creation of a female divinity in order to overcome the presence of the masculinity. The author considers that in a third feminist generation, the recognition of the intrinsic wealth of the feminine nature “sameness”, should come to surface.